Pengaruh Likuiditas, Solvabilitas, Aktivitas terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Intervening (Studi Kasus pada Perusahaan Subsektor Rokok yang Terdaftar di BEI Periode 2016-2022) - Apriliana, Larasati; Sodik, M.; Puspitosarie, Endah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2024)
Indonesia is one of the countries that has the largest source of income from excise taxes on tobacco products, especially those produced from cigarettes. To maintain the cigarette industry to develop further, one way is to go public, which allows investors to invest capital to help the company grow and increase its profitability. The aim of this research is to determine the influence of liquidity, solvency and activity on company value with profitability as the mediator. The research method used is quantitative with an SEM approach. Data collection techniques use secondary data. The data instrument used is Structural Equation Model Analysis (SEM) and hypothesis testing using Smart PLS software. The results obtained in this research mean that liquidity and solvency have no effect on company value and profitability, activity has an effect on company value and profitability. However, profitability itself cannot mediate between the independent variable and the dependent variable in this research.